The association between fatigue and apathy in patients with either Parkinson's disease or multiple sclerosis. Issue 9 (September 2015) - Cochrane, Graham D.; Rizvi, Syed; Abrantes, Ana M.; Crabtree, Brigid; Cahill, Jonathan; Friedman, Joseph H.
Abstract Objective Fatigue and apathy are common symptoms in both multiple sclerosis (MS) and Parkinson's disease (PD). Both symptoms are considered "amotivational"—fatigue is a lack of energy to start or complete an action and apathy is a loss of interest in activities. Whether the two symptoms are related to each other is not known. The present study sought to investigate the prevalence and severity of fatigue and apathy in MS and PD, and the relationship between the two. Methods The Fatigue Severity Scale (FSS) and the Apathy Scale (AS) were administered to 89 consecutive PD and 73 consecutive MS subjects. Results The mean FSS score for PD subjects was 4.46 and 5.01 for MS; the average total AS score for PD was 12.4 and 12.5 for MS. Using a cutoff of >4.0 on the FSS to assess fatigue, 64% of PD subjects and 74% of MS subjects suffered from severe fatigue. Using an AS cutoff score of >14.0 to determine apathy, 57% of PD subjects and 52% of MS subjects were apathetic. There was a significant correlation between FSS score and AS score in both disorders. FSS average scores and AS total scores were significantly correlated with motor severity in PD but not in MS. Duration of disease was not correlated with either scale scores in either disorder. Discussion Results confirm that AS and FSS are correlated with each other in both disorders and that MS subjects rate their fatigue significantly higher.